Here's the pitch : how to pitch your business to anyone, get funded, and win clients - Soorjoo, Martin, 1967- (Hoboken, NJ : John Wiley & Sons, 2012)
'Advice for every pitch situation a modern day entrepreneur will encounterWhether you're pitching for funding, the media, or to potential customers and partners, to survive and succeed as an entrepreneur, you have to know how to deliver a high-impact pitch. Here's the Pitch reveals the secrets to a winning mindset,teaching you a range of powerful techniques to get your audience to take action. You'll learn the same strategies and tactics that have been used to raise millions of dollars, secure partnerships, and win big sales contracts.Here's the Pitch provides advice for every possible pitch situation, including virtual and web 2.0 pitches. This book: Helps readers to develop a winning mindset Demonstrates proven, successful pitch techniques Offers step-by-step advice for preparing your pitch Examines a range of pitch scenarios an entrepreneur might encounter Don't lose out on your next big sale, bid for exposure, or investment proposal for lack of skills. Here's the Pitch provides a complete toolkit that will enable you to deliver a confident, engaging, and successful pitch'--
Includes bibliographical references (p.189-190) and index.
Keywords: Business presentations; Entrepreneurship; Success in business